Utilization of Integrated Community Case Management and Its Factors in Southern Ethiopia: Facility Based-Cross-Sectional Study - Samuel Yohannes; Yitagesu Habtu; Bereket Abreham; Menen Ayele (Advances in Public Health)
Background. An integrated community case management (ICCM) program fosters child health care seeking and access to appropriate treatment for illnesses in children at the community level in Ethiopia. There is paucity of evidence to the utilization of ICCM services by mothers/child caregivers in rural Sothern Ethiopia. Hence, the aim of this study was to determine the utilization of integrated community case management (ICCM) and its factors among mothers/child caregivers in rural Southern Ethiopia. Methods. A multistage sampling technique was used to select study participants in health care facilities offering child health care services. An exit interview was conducted on 574 mothers/child caregivers in randomly selected public health centres. Data were entered using Epi Info and transported to SPSS version 20 for analysis. Results. Only less than a quarter of participants visited health posts for ICCM services during the study period. Those study participants who have not heard about ICCM service before the survey were about 6.53 times more likely not to use the services as compared to those who have heard about the service. Participants who were not members of the women’s development team were about 2.23 times more likely not to utilize ICCM services when compared to their counterparts. Conclusion. The study shows low utilization of ICCM service by children less than five years. Prior information about ICCM services and membership in the health development army was significantly associated with ICCM use. Therefore, our finding may suggest the need for advocacy to increase participation in the health development army and information education to increase the level of awareness and formal education efforts.